Empowerment of Reuse, Reduce and Recycle Programme (Kang Pisman) In Bandung - Adibowo, R; Wibiksana, I G (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The Reuse, Reduce, and Recycle Program kurangi, pisahkan dan manfaatkan (Kang Pisman) is a waste management program which basically uses the principle of zero waste. The success of waste management is determined by the involvement of the community, government and the private sector working together. To improve the community's capacity in waste management, the Bandung City Government has implemented an empowerment program through the Kang Pisman program. Regarding empowerment, in essence, it is to strengthen the power (ability) so that the community is independent, therefore empowerment can be interpreted as a capacity building process. Strengthening the capacity here to foster community participation with three factors, namely strengthening individual capacity, institutional capacity and network capacity. This study is intended to obtain data and information about Community Empowerment through the Reduce, Separate and Take advantage of Bandung City, while the objectives achieved in writing this study include: to identify and analyze the capacity of individuals in the community on Community Empowerment through The Reduce, Sorting Trash and Benefit (Kang Pisman) Program in Bandung City, to identify and analyze institutional capacity in Community Empowerment through The Reduce, Sorting Trash and Benefit (Kang Pisman) Program in Bandung City, to identify and analyze network capacity in Community Empowerment through the Reduce, Separate and Take advantage of (Kang Pisman) in Bandung City.The method used is descriptive method with a qualitative approach. Data collection techniques using library research and field studies. namely nonparticipant observation, interviews and documentation. The technique of determining informants for the Bandung City Environment and Sanitation Service apparatus uses purposive techniques and for the community using the Accidental technique. The results of this study indicate that strengthening the individual capacity for community empowerment through the Kang Pisman program in Bandung City in increasing the capacity of the personality to increase the ability and independence of the community in managing waste at the source has not been implemented thoroughly and optimally. Strengthening institutional capacity through the Kang Pisman program in planning, implementation and supervision has not been optimal. Strengthening network capacity through the Kang Pisman program in Cihaurgeulis Village in cooperating with related organizations such as RT, RW, Kelurahan and environmental care organizations has not been optimal.